Application of Toolbox Diagnosis of Sustainability 4.0 in Manufacturing Operations: Sustainability Integration in the Context of Industry 4.0 - Arguelles, Carmen G.; Torres, Vianey; Noriega, Salvador (2024)
Background: This paper describes the development of a toolbox for measuring the state of sustainability in industrial plants adopting Industry 4.0 (I4.0), using a diagnosis of Sustainability 4.0 (S4.0) (i.e., the integration of sustainable practices with I4.0 tools) as a business strategy, based on the Sustainable Development Goals (SDGs) of the United Nations (UN).